Mechanobiological feedback loops and quantitative decision thresholds in organ fibrosis: Translational principles for antifibrotic therapy - Amedeo Lonardo; Ralf Weiskirchen (Journal of Cell Communication and Signaling, 2026)
Abstract Multiorgan fibrosis is a complex, maladaptive response to chronic injury, where the extracellular matrix (ECM) shifts from serving merely as a structural framework to becoming an active, sustained contributor to disease progression. We propose a unifying mechanobiological framework in which chronic injury promotes fibroblast activation and ECM remodeling, whereas the stiffened and remodeled ECM feeds back through integrins, mechanosensitive ion channels, collagen receptors, and Hippo‐YAP/TAZ signaling to sustain fibrogenesis. Regulation of this process is governed by bidirectional feedback between cellular signaling and the matrix's physical properties across organs such as the lung, heart, liver, and kidney. This narrative review article presents recent advances in understanding mechanisms of cell–cell and ECM communication, paratensile signaling, mechanical feedback loops, cellular crosstalk and secretomes, quantitative therapeutic thresholds, and translational strategies for tissue remodeling. These developments collectively offer promising insights for the development of novel pharmacological agents targeting mechanotransduction pathways, ECM normalization, and cell‐specific sensitization. We further define quantitative thresholds as diagnostic, action, and response thresholds that may support clinical decisions such as referral, treatment initiation, therapeutic monitoring, and clinical‐trial enrichment. Finally, we provide specific details regarding the treatment of liver fibrosis before concluding with research agenda.